22 Public and patient involvement in prehospital care research development – designing the rapid 2 trial. (26th April 2019) - Evans, Bridie; Bulger, J; Ford, S; Foster, T; Goodacre, S; Jones, S; Keen, L; Longo, M; Lyons, R; Pallister, I; Parry, L; Rees, N; et al.
Abstract : Background: Involving patients and public members in research helps ensure evidence is relevant, accountable and high quality. Public and patient involvement (PPI) is required in many funding applications. We aimed to involve public contributors in designing a research bid about prehospital management for hip fracture. Method: We recruited two public contributors with experience of hip fracture and prehospital care to our research team of academic, clinical and managerial partners developing the RAPID 2 proposal evaluating paramedic administration of Fascia Iliaca Compartment Block, a local anesthetic injection into the hip. We supported them to consult with a public/patient group and identify patient priorities to inform our decisions. We held research development meetings and shared project drafts to gain views, share decisions and amend documents. Results: Consultation responses suggested patient priorities after hip fracture were to return home, recover mobility and gain independence. These views guided our decisions on setting primary outcomes which were length-of-hospital-stay and health-related quality-of-life. Their concern about the study design causing delayed access to treatment meant we decided to identify common exclusion criteria before randomisation to expedite access to pain management and reduce attrition. Public contributors also agreed patients should be offered an incentive for completing and returning questionnaires to enhance data completeness. Conclusion: Involving public contributors enabled the research team to identify patient-prioritised outcomes and adjust the proposed study design to reflect these in the proposal. Public contributors will remain involved if funding is awarded to ensure patient perspectives inform all stages of research management and dissemination. Conflict of interest: None. Funding: PRIME Centre Wales.